FAKTOR PENYEBAB PENGEMBANG MEMILIH LOKASI PERUMAHAN DI KECAMATAN MARTAPURA KOTA KABUPATEN BANJAR - Uun Wantri; Eva Alviawati; Deasy Arisanty (Universitas Lambung Mangkurat, 2016)
The background of this study is the large amount of housing that require a lot of land for a place to stay. The residence is one of the primary needs of man apart from clothing and perspective. In order to meet the housing needs, the government in collaboration with the private sector in the provision of housing activity. The phenomenon is happening shows that of the 19 District in Banjar, District Martapura city is an area of residential development at most. Added housing construction in the district Martapura city built by a housing developer 39, an area of 42.01 km city Martapura Subdistrict in 2010-2015. The population in this study are all housing developers in the district of the city Martapura total of 39 developers. The sample in this study was the same as the total population . Data collection techniques in this study done by questionnaire , observation and document study method . Analyzed using descriptive statistics with an analysis of the percentage of each of the factors causing housing developers choose the location based on the questionnaire answers housing developers .The results showed that factors that affect housing developers choose the most dominant location chosen by developers of housing in the district of the city Martapura as decisive factors assessed , namely : economic factors which ranks first chosen by 21.54 % of developers , and social factors that are out second was chosen by 13.68 % of developers .Keywords: Factors causing the developer choose the location of housing housing developers